Exciton condensation in quantum wells. Exciton hydrodynamics. The effect of localized states - Sugakov, V.I. (Condensed Matter Physics, 2014)
The hydrodynamic equations for indirect excitons in the double quantum wells are studied taking into account 1) a possibility of an exciton condensed phase formation, 2) the presence of pumping, 3) finite value of the exciton lifetime, 4) exciton scattering by defects. The threshold pumping emergence of the periodical exciton density distribution is found. The role of localized and free exciton states is analyzed in the formation of emission spectra. Проведено аналiз рiвнянь гiдродинамiки екситонiв у квантовiй ямi. Рiвняння враховують 1) можливiсть
фазового переходу в системi, 2) присутнiсть зовнiшньої накачки, 3) скiнчений час життя екситонiв, 4) розсiяння екситонiв на дефектах. Визначно порогову накачку утворення перiодичного розподiлу екситонної
густини. Дослiджується вплив локалiзованих i вiльних екситонiв на формування спектрiв випромiнювання.